If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 6(7x + -1(7 + -2y + 2x) + 5y) = 0 Reorder the terms: 6(7x + -1(7 + 2x + -2y) + 5y) = 0 6(7x + (7 * -1 + 2x * -1 + -2y * -1) + 5y) = 0 6(7x + (-7 + -2x + 2y) + 5y) = 0 Reorder the terms: 6(-7 + 7x + -2x + 2y + 5y) = 0 Combine like terms: 7x + -2x = 5x 6(-7 + 5x + 2y + 5y) = 0 Combine like terms: 2y + 5y = 7y 6(-7 + 5x + 7y) = 0 (-7 * 6 + 5x * 6 + 7y * 6) = 0 (-42 + 30x + 42y) = 0 Solving -42 + 30x + 42y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '42' to each side of the equation. -42 + 30x + 42 + 42y = 0 + 42 Reorder the terms: -42 + 42 + 30x + 42y = 0 + 42 Combine like terms: -42 + 42 = 0 0 + 30x + 42y = 0 + 42 30x + 42y = 0 + 42 Combine like terms: 0 + 42 = 42 30x + 42y = 42 Add '-42y' to each side of the equation. 30x + 42y + -42y = 42 + -42y Combine like terms: 42y + -42y = 0 30x + 0 = 42 + -42y 30x = 42 + -42y Divide each side by '30'. x = 1.4 + -1.4y Simplifying x = 1.4 + -1.4y

| 14x-8=13x-10 | | MN+4MN+5MN-10MN+5MN= | | 1(x+1)=5 | | 1+4x^2=8X | | 6k+7=4+12k | | 9t^2+14-17t+6t-8t^2=0 | | X^2+6x=9 | | 10m-4(3m+7)+6m=0 | | 5x^10-4x^11=1 | | 91-7x=11x+15 | | 0=5x^10-4x^11-1 | | 10-10x=74-24x | | 2x+18=66 | | y=5x^10-4x^11-1 | | -73-9x=9x+17 | | 10km-km+5km-9km+3km= | | 4x+31=13x-68 | | 91-5x=10x+16 | | 2+7m= | | 5+5g= | | 8x-25=55 | | 3BC+BC+2BC+10BC-5BC= | | 3n+6p= | | x-2x+4x-8x=8 | | 3(x+5)=90 | | 3(4x+5)=-45 | | 5+2m+1= | | 7+7p= | | 4(x-6)-4(x-8)=-10 | | 7=5(1x-4)+2 | | 7q+8r-6r= | | 0.6666666y+5y=70-y | | 5x+2y=18 | | 4a+9a+2+4a= | | 2x-3y=11 | | 18=2(1g+4)+3(2g-6) | | 9+16x^2-24x=0 | | -4+6t-6= | | x-y=4v | | 3x+24=y | | 2n+4n-4n= | | 6(3.5+1r)-1=7r-r | | 10BC+7BC= | | 4t+7t+tu+8t= | | x=27 | | 8+1+9t= | | 5k+3k-4k= | | 8+7d= | | 3+k+7k= | | 1+2t= | | 4s+st= | | 4d+6d-7d= | | 5(x+2)=3x+7 | | -212b=-424 | | 8h-2h+10h= | | 7s+2=5-3s | | 6p-p= | | 4r-1=7 | | 2z+3yz-6z+2yz+y-z-4y= | | 5r-3r+7r= | | 3k-3k+8k+8km= | | 4x+27=x-3 | | 10n+8p= | | 6t-3t= | | 6+2s+2(8s+8)= |

- Equations solver - equations involving one unknown
- Quadratic equations solver
- Percentage Calculator - Step by step
- Derivative calculator - step by step
- Graphs of functions
- Factorization
- Greatest Common Factor
- Least Common Multiple
- System of equations - step by step solver
- Fractions calculator - step by step
- Theory in mathematics
- Roman numerals conversion
- Tip calculator
- Numbers as decimals, fractions, percentages
- More or less than - questions